POST-TRAINING EVALUATION: BEHAVIOR OF COMMUNITY HEALTH CENTER MANAGEMENT TRAINING ALUMNI - tuti surtimanah; Setia Kahadiwan; Lilis Sriyani; Rina Rostarina; Tati Nurhayati; Irna Avianti (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat)
The implementation of Community Health Center (CHC) management is still considered suboptimal, therefore training is carried out for health center personnel held at the West Java Provincial Health Training Unit, which is an accredited institution. In 2022, Community Health Center management training will be carried out for personnel who will lead programs at CHC and the results need to be evaluated for improvement and feedback. The purpose of the research was to determine the behavior of CHC management training alumni in implementation in their workplaces. The research method is a mixed methods design, explanatory sequential design. The population of alumni of the 2022 training was 60 people, with a sample sample according to criteria of 49 people for quantitative research, and 13 alumni informants, boss and colleagues who were selected purposively. Quantitative data collection through the distribution of questionnaires in the google forms, analyzed descriptively, comparatively and correlatively. Qualitative data collection through in-depth interviews, then processed using the framework analysis approach. The results of the research showed that less than half of the alumni had good category in health center management knowledge and skills, and 7 out of 10 alumni had good category attitudes. Most have implemented planning and implementation as stages of CHC management, but only 3 out of 5 alumni have implemented monitoring and control assessments. The conditions revealed are the basis for the need for leadership and organizational support and assistance in implementing CHC management which is expected to support the achievement of quality health services for the community.